Prognostic risk factors and the role of systemic inflammatory response index in predicting outcomes for non-muscle-invasive bladder cancer - Gui, Qi; Guo, Hongwei; Liu, Taiyang; Wen, Xiuhua; Jiao, Xiang (Frontiers in Oncology, 2025)
BackgroundNon-muscle-invasive bladder cancer (NMIBC) presents a variable prognosis, with a significant risk of recurrence and progression. Traditional clinicopathological factors provide limited prognostic accuracy, necessitating additional biomarkers. This study aimed to evaluate the prognostic role of the systemic inflammatory response index (SIRI) and traditional risk factors in predicting outcomes in NMIBC patients.MethodsWe retrospectively analyzed 158 NMIBC patients who underwent transurethral resection of bladder tumor (TURBT) between January 2021 and October 2023. Patients were stratified into recurrence/non-recurrence and progression/non-progression groups. Clinical and pathological characteristics were compared using Chi-square tests, t-tests, or Fisher’s exact tests as appropriate. Receiver operating characteristic (ROC) analysis identified the optimal SIRI cutoff, which was used for Kaplan-Meier survival analysis and Cox regression to assess independent prognostic factors for progression-free survival (PFS).ResultsThe optimal SIRI cutoff value for predicting progression was 0.716 (area under the curve [AUC] = 0.689, sensitivity = 0.689, specificity = 0.718). Patients with SIRI ≥ 0.716 exhibited significantly higher progression risk (P = 0.012) and poorer PFS (Log-rank P < 0.05). Multivariate Cox regression confirmed tumor count (HR = 3.273, 95% CI: 1.003–10.691, P = 0.049), primary diagnosis status (HR = 2.563, 95% CI: 1.012–7.214, P = 0.045), and high SIRI (HR = 2.979, 95% CI: 1.110–8.027, P = 0.031) as independent predictors of PFS. Recurrence analysis further revealed that high SIRI was associated with markedly increased recurrence rates in both Ta (50.0% vs. 6.2%, P < 0.001) and T1 subgroups (73.9% vs. 32.3%, P < 0.001).ConclusionsSIRI is a significant predictor of disease progression in NMIBC, although it is not associated with RFS. When combined with clinicopathological factors such as tumor stage, grade, count, and primary diagnosis status, SIRI can enhance risk stratification in NMIBC, aiding personalized management.